TANGGUNG JAWAB YURIDIS RUMAH SAKIT TERHADAP PERLINDUNGAN HAK PASIEN SELAKU PENGGUNA JASA PELAYANAN KESEHATAN - Rusniawati Ayu Safitri (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT Every human being has been born human rights. One of the human rights that are recognized and respected in Indonesia is the right to health. The right to health is set directly in the Indonesian constitution, namely in Article 28H of the Constitution of the Republic of Indonesia Year 1945, which stipulates that "Everyone has the right to live in welfare and spiritual birth, residence, and obtain environmental good and healthy and receive medical care ". The importance of health requires effort to achieve health in accordance with the constitutional mandate and legislation as well as the concept of the importance of health in many aspects. If the patient experiences a loss due to the negligence or fault of health workers, the patient is entitled to receive compensation, because the positions as the patient suffered losses caused by the hospital as a result of default or unlawful acts. The relationship between doctors and patients have a contract (the doctrine of social-contract), which gives the public profession of the right to self-regulating (autonomous profession) the obligation to provide a guarantee that the professionals who practice only professionally competent and who carry out the practice of his profession in accordance with the standards. Hospital paradigm change of social institutions into socio-economic institutions that can be used as subjects of law. Therefore, it should be anticipated with clarity about the rights and responsibilities of each stakeholder in the management of the hospital, which will be organized into Hospital bylaws (Statute). Hospital as a health care institution whose energy multi-disciplinary terms with funds and technology. So it does not close the possibility of conflicts between interested parties between the customer with palayanan providers, as well as between the owner and the manager or manager with his staff. Hospital Bylaws (Statute) is one form of written rules that apply in a hospital in order to protect all parties concerned is good and right by a sense of justice.. Keywords : protection, rights, patients